IJCM_417A: Internet health information seeking and its effect on patient-doctor relationship and satisfaction among patients attending a tertiary care hospital in Mangalore - Aggarwal Shreyas; Suresh Aakriti; Jindal Disha; Trikha Radhika; Rekha T; Kumar Nithin; Unnikrishnan Bhaskaran; Mithra Prasanna; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: The doctor-patient relationship is a fundamental and essential component of healthcare that plays a critical role in patient outcomes, trust, and overall quality of care. Internet-based health information has been found to have both positive and negative effects on patients. Objectives: To assess the internet health-seeking behaviour among patients, and its effect on the doctor-patient relationship Methodology: In this facility-based cross-sectional study, 110 patients were assessed regarding their internet health-seeking behaviour and its effect on the doctor-patient relationship. Patient-Doctor Depth-of-Relationship Scale and Patient Satisfaction Questionnaire - Short form (PSQ-18) was used to assess the relationship. A comparison of patient satisfaction scores and doctor-patient relationship scores among those who use the internet for seeking health-related information with those who do not was done by independent t-test and P < 0.05 will be considered to be a statistically significant difference. Results: Sixty-seven-point three per cent use the internet for health-related information. Most of the patients felt satisfied with their medical care but there was still some scope of improvement in the domains of communication and the time devoted by the doctor to the patient. The overall level of patient satisfaction was above average. Our study also showed that 77.2% of the study participants had a good relationship with their doctor. Conclusion: In our study, we found that the internet using study participants were found to have an above average satisfaction with their doctors.